INTEGRATED RESORT'S RETAIL AND ENTERTAINMENT SPACE PLANNING AND MANAGEMENT AND ITS IMPACT ON VISITOR'S SATISFACTION (MARINA BAY SANDS AND RESORT WORLD SENTOSA) - LEE LING HUI MELISSA (2012)
Bachelor's